Pengolahan Limbah Cair Tahu Menggunakan Media Lekat Sarang Tawon - Cahyani, Nanda Dwi; Situmorang, Mairo; Azhura, Tiara; Apriani, Isna (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The high amount of tofu production every day is directly proportional to the waste produced every day and this is one of the environmental problems, considering the large number of tofu industries in Pontianak City, in line with this. Plastic botoh waste is found in every corner of the city, so this is minimized by making wasp nest sticky media for the tofu liquid waste treatment process. Anaerobic-aerobic biofilter using plastic bottles as the attachment media and filters for activated carbon, zeolite, gravel, palm fiber and aquarium foam. This reactor has dimensions of 70 x 20 x 30 cm and consists of 3 parts, namely an anaerobic tank, an aerobic tank and a filter tank. Before processing, plastic bottles are seeded for 7 days by adding EM4 and brown sugar as nutrients so that microorganisms can grow and form biofilms on the plastic bottles. Then acclimatization was carried out for 3 days with a concentration of tofu liquid waste of 50%, 75% and 100% so that microorganisms could adapt to tofu liquid waste. The results of this study indicate that the efficiency of decreasing BOD and COD content is 75.6% and 72.6%, respectively, and there is an increase in the pH value, where before processing the initial pH is 3.71 and after processing it becomes 7.25.Keywords: Anaerobic-aerobic biofilter, tofu liquid waste, BOD, COD, pH and plastic bottles